The Lists of Churches, Religious Communities and Places of Worship in the Towns of Russia in the Second Half of the 1920s Presented to the All-Russian Central Executive Committee - Kovaleva Irina (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2016)
The originals of the documents published in this article are being kept in the State Archive of the Russian Federation. The documents throw light upon diﬃ cult period in the history of Russian Orthodox Church, reﬂ ect schisms, separations of the 1920s and splitting up of the religious communities used by the godless state for the war against the Church.